Construction of an in vivo System for Functional Analysis of the Genes Involved in Sex Pheromone Production in the Silkmoth, Bombyx mori - Moto, Ken-Ichi; Matsumoto, Shogo (Frontiers in Endocrinology, 2012)
Moths produce species-specific sex pheromones to attract conspecific mates. The biochemical processes that comprise sex pheromone biosynthesis are precisely regulated and a number of gene products are involved in this biosynthesis and regulation. In recent years, at least 300 EST clones have been isolated from Bombyx mori pheromone gland (PG) specific cDNA libraries with some of those clones (i.e., B. mori PG-specific desaturase1 (Bmpgdesat1), PG-specific fatty-acyl reductase (pgFAR), PG-specific acyl-CoA-binding protein (pgACBP), B. mori fatty acid transport protein (BmFATP), B. mori lipid storage droplet protein-1 (BmLsd1)) characterized and demonstrated to play a role in sex pheromone production. However, most of the EST clones have yet to be fully characterized and identified. To develop an efficient system for analyzing sex pheromone production-related genes, we investigated the feasibility of a novel gene analysis system using the upstream region of Bmpgdesat1 that should contain a PG-specific gene promoter in conjunction with piggyBac vector-mediated germ-line transformation. As a result, we have been able to obtain expression of our reporter gene (enhanced green fluorescent protein) in the PG but not in other tissues of transgenic B. mori. Current results indicate that we have successfully constructed a novel in vivo gene analysis system for sex pheromone production in B. mori.